After the ancestors an anthropologist's story - Beatty, Andrew; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2015)
Set on an isolated Indonesian island, this is the gripping true story of a fieldworker's experience of living in a tribal society during a period of crisis. Featuring a cast of unforgettable characters, After the Ancestors follows a bitter feud between rivals as it escalates into murder, intrigue and revenge. A vivid account of life within a radically different world, it also portrays a unique culture undergoing the transition from tribalism to modernity. A century of alien rule has left the island, once famous for its warrior ethos, with a hybrid culture. As the possibilities for heroic action recede, men raised to be orators and over-reachers rather than church elders and peasants find themselves occupying a stage too small for their personalities. 'Where can we turn', asks one tribesman, 'we who come after the ancestors?' A revenge tragedy for modern times, After the Ancestors will be enjoyed by anthropologists and general readers alike.
Machine generated contents note: List of illustrations; Preface; People; Prologue; 1. The statue; 2. House key; 3. Among women; 4. Blood brothers; 5. Daggers and debutants; 6. Stormy Sunday; 7. Three things that matter; 8. The making of great men; 9. A game of chess; 10. Cholera song; 11. Progress; 12. Strangers and brothers; 13. Exile and return; 14. Field work; 15. The chicken's neck; 16. Good deaths and bad deaths; 17. First family; 18. Blessing; 19. Half an egg; 20. Waiting; 21. Death of a chief; 22. Ama Jonah at bay; 23. Unravelling; 24. The ethnographer and his double; Epilogue.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Beatty, Andrew -- Travel -- Indonesia -- Nias Island; Electronic books; Niasese (Indonesian people) -- Indonesia -- Nias Island -- Social life and customs; Niasese (Indonesian people) -- Indonesia -- Nias Island -- Social conditions; Nias Island (Indonesia) -- Social life and customs; Nias Island (Indonesia) -- Social conditions